GABA mediated aggression in female mice. - Bicakci, Matthew.; Lauze, Meghan.; Newman, Emily.; Miczek, Klaus.; DeBold, Joseph. (Tufts University. Tisch Library., 2017)
Alcohol and Violence: Most violent crime involves the consumption of alcohol. While most violent crime is committed by men, women can also become more aggressive under the influence of alcohol. Individual Variability: Only a subset of individuals become aggressive after intake of alcohol. This can be seen in humans, as well as in animals (Miczek et al ,1998). Brain Mechanisms: Alcohol and benzodiazepines have a facilitating effect on GABAA receptors, the main inhibitory receptor in the brain. At low doses, these can alter an individual’s perception of social cues which leads to increases in aggressive behavior. However, most research on heightened aggression in mammals has been conducted in males. Background Results: Aim 1: To determine if GABA-mediated heightened aggression can be modeled in female mice using alcohol and the benzodiazepine midazolam Aim 2: To determine any differences in expression of heightened aggression between the sexes. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.